‘The Elderly are More Comfortable at Home Than at The Health Facility’. Primary Care Provider Notions On Instituting Community-Based Geriatric Support in Uganda - Ssensamba, Jude Thaddeus; Nakafeero, Mary; Musana, Hellen; Amollo, Mathew; Ssenyonjo, Aloysius; Kiwanuka, Suzanne N. (Research Square, 2021)
Understanding of the most economical and sustainable models of providing geriatric care to Africa’s rising ageing population is critical. In Uganda, the number of old adults (60 years and above) continues to rise against absence of policies and guidelines, and models for providing care to this critical population. Our study explored public primary health care provider views on community-based geriatric support (CBGS) as an adaptable model for delivering geriatric care in Uganda’s resource-limited primary public health care settings. Methods We interviewed twenty key informants from four districts of Bukomansimbi, Kalungu, Rakai, and Lwengo in Southern Central Uganda. Respondents were leads (in-charges) of public primary health units that had spent at least six months at the fore said facilities. All interviews were audio-recorded, transcribed verbatim, and analysed based on Hsieh and Shannon’s approach to conventional manifest content analysis. Results During analysis, four themes emerged: 1) Structures to leverage for CBGS, 2) How to promote CBGS, 3) Who should be involved in CBGS, and 4) What activities need to be leveraged to advance CBGS? The majority of the respondents viewed using the existing village health team and local leadership structures as key to the successful institutionalization of CBGS; leveraging community education and sensitization using radio, television, and engaging health workers, family relatives, and neighbors. Health outreach activities were mentioned as one of the avenues that could be leveraged to provide CBGS. Conclusion Provider notions pointed to CBGS as a viable model for instituting geriatric care in Uganda’s public primary healthcare system. However, this requires policymakers to leverage existing village health team and local governance structures, conduct community education and sensitization about CBGS, and bring onboard health workers, family relatives, and neighbors.
Keywords: Community-based geriatric support; Uganda; Health providers; Notions; Old Adults; Primary Health Care; The elderly